Salmonella enterica subsp. II serovar 4, 5, 12:a:- may cause gastroenteritis infections in humans. (31st December 2022) - Yan, Meiying; Zhou, Yongming; Cao, Yang; Li, Zhenpeng; Lu, Xin; Pang, Bo; Wang, Shukun; Kan, Biao
ABSTRACT: Some serovars of Salmonella are not or rare found to cause salmonellosis in human. In our clinic-based surveillance, three rare Salmonella 4, 5, 12:a:- strains were recovered from three patients with diarrhea. To explore their genetic and epidemiological characteristics and pathogenesis, we conducted whole-genome sequencing, in vitro invasion assays in mammalian cells, and in vivo virulence assays in an animal model. The three isolates had indistinguishable molecular patterns and similar genome sequences, and clustered together with an isolate from edible fish traded among countries. The isolates had biochemical reactions identical with those of Salmonella subspecies enterica but belonged to subspecies salamae according to genome phylogeny, revealing a new serovar, S. enterica subsp. II serovar 4, 5, 12:a:-. The strains contained multiple virulence genes, elicited temporary bacteremia and enteritidis and caused cell damage in the mouse liver and cecum. This study provides evidence that this new Salmonella salamae serovar can infect humans and cause clusters of cases, and whole-genome sequencing detection and surveillance of Salmonella can help to accurately define Salmonella classification and clonality, improve diagnosis, facilitate outbreak detection and aid in the source tracing of salmonellosis epidemics.